Methanol : science and engineering - Basile, Angelo; Dalena, Francesco (Elsevier, 2018)
Methanol: Science and Engineering provides a comprehensive review of the chemistry, properties, and current and potential uses and applications of methanol. Divided into four parts, the book begins with a detailed account of current production methods and their economics. The second part deals with the applications of methanol, providing useful insights into future applications. Modeling of the various reactor systems is covered in the next section, with final discussions in the book focusing on the economic and environmental impact of this chemical. Users will find this to be a must-have resource for all researchers and engineers studying alternative energy sources.